Effects of different rates of nitrogen and pinching on yield and yield attributes of African marigold (Tagetes erecta L.) - Pandey, Madan; Subedi, Shashi; Khanal, Prakash; Chaudhary, Prabin; Adhikari, Anil; Sharma, Tej Prasad; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
Proper pinching practice and the optimum rate of nitrogen (N) enhance the production of marigold. An experiment was conducted at a farmer’s field in Gadawa-4, Gangaparaspur, Dang, Nepal from July 2018 to November 2018 to investigate the effects of different rates of nitrogen and pinching on yield and yield attributes of African marigold (cv. Kolkata Local). Two factorial experiment was laid in the Randomized Complete Block Design (RCBD) with three replications. There were eight treatments, consist of four rates of nitrogen (0, 50, 100 and 150 kg/ha) and two levels of pinching (pinching and non-pinching). The maximum plant height (89.70 cm), the diameter of flower (4.29 cm) and the fresh weight per flower (4.32 g) and early days to 50% flowering (61.58) were obtained at non- pinching. The highest number of flowers (60.66), yield per plant (237.49 g) and yield per hectare (9.89 t/ha) were obtained with pinching. The highest plant height (92.20 cm) was recorded at 150 kg/ha of N but the highest yield per plant (238.18 g) and yield per ha (9.91 t/ha) was obtained at 50 kg/ha of nitrogen application. No significant effect was noted on the days to 50% flowering, number of flowers per plant, fresh weight per flower and diameter of flowers by different rates of nitrogen. The interaction of pinching and different rates of nitrogen showed non- significant effect on yield per plant and yield per ha. But, the combination of pinching and nitrogen rates at 50 kg/ha recorded the maximum yield per plant (249.20 g) and yield per ha (10.36 t/ha). Hence it is suggested to use pinching practice with optimum application of nitrogen @ 50 kg/ha to obtain high yield of marigold.